Race and racism in literature - Wilson, Charles E. 1961-; Gale Group (Westport, Conn. Greenwood Press, 2005)
"Address issues of race and racism as presented in novels of varying racial, ethnic, or cultural perspectives. Focuses mainly on racial oppression in the United States, however some chapters do also assess the imposition of racist attitudes on foreign shores."--GVRL description.
Mark Twain, The adventures of Huckleberry Finn (1885) -- Richard Wright, Native son (1940) -- Harper Lee, To kill a mockingbird (1960) -- Jose Antonio Villarreal, Pocho (1959) -- Sandra Cisneros, The house on Mango Street (1984) -- Margaret Craven, I heard the owl call my name (1973) -- Leslie Marmon Silko, Ceremony (1977) -- Arlene J. Chai, The last time I saw mother (1995) -- Nora Okja Keller, Fox girl (2002) -- Rita Ciresi, Sometimes I dream in Italian (2000) -- Chaim Potok, The chosen (1967) -- Amy Wilentz, Martyrs' crossing (2001).
Electronic reproduction.
Keywords: Twain, Mark -- 1835-1910.; Wright, Richard -- 1908-1960.; Lee, Harper; Villarreal, Jose Antonio; Cisneros, Sandra; Craven, Margaret; Silko, Leslie -- 1948-; Chai, Arlene J; Keller, Nora Okja; Ciresi, Rita; Potok, Chaim; Wilentz, Amy; American literature -- History and criticism; Racism in literature; Literature and society -- United States; Race in literature; Electronic books